Lipoperoxidação, perda de viabilidade celular e diminuição da liberação de IL-8 de neutrófilos humanos na presença de corpos cetônicos - Gileno, M. C. [UNESP]; Ximenes, Valdecir Farias [UNESP]; Da Fonseca, Luiz Marcos [UNESP] (My University, 2009)
Type-1 diabetes patients suffer from frequent episodes of acidosis caused by an increased fatty acid metabolism and consequently increased plasma level of acetoacetate (AcAc) and β-hydroxybutyrate (β-HOB). This article describes a study of the effects of pathological concentrations of AcAc and β-HOB on lipoperoxidation, cell viability and the release of the CXCL8 (IL-8) cytokine by activated neutrophils. Neutrophils from healthy donors were isolated by density gradient (Histopaque® 1077/1119) and incubated with the ketone bodies. Lipoperoxidation was determined as thiobarbituric acid reactive substances (TBARS). The cell viability was evaluated by the release of intracellular lactate dehydrogenase. The release of CXCL8 was measured by ELISA in a 24-h culture of opsonized zymosan-stimulated neutrophils. AcAc, but not β-HOB, provoked a dose-dependent increase in the neutrophil membrane lipoperoxidation (p<0.05; r =0.9915). In the cytotoxicity assay, a dose-dependent release of LDH was observed when the neutrophils were incubated with AcAc in concentrations up to 40 mM (p<0.05). β-HOB was devoid of effect. The release of CXCL8 was inhibited by AcAc and β-HOB in a dose-dependent manner. In conclusion, these results suggest that the accumulation of ketone bodies in diabetic patients could be involved in their usually increased susceptibility to infection.

Portadores de diabetes tipo-1 são acometidos por episódios freqüentes de acidose causada pelo aumento no metabolismo de ácido graxos com conseqüente acúmulo de acetoacetato (AcAc) e β-hidroxibutirato (β -OB). Neste trabalho estudou-se o efeito de concentrações patológicas destes metabólitos na lipoperoxidação, viabilidade e liberação da quimiocina CXCL8 (IL-8) por neutrófilos em cultura. Neutrófilos de indivíduos saudáveis foram isolados por gradiente de densidade (Histopaque 1077/1119) e incubados com os corpos cetônicos. A lipoperoxidação foi determinada pela presença de substâncias reagentes ao ácido tiobarbitúrico (TBARS). A viabilidade celular foi avaliada pela liberação da enzima lactato desidrogenase. A liberação de CXCL8 para o meio extracelular foi medida após cultura de 24 horas de neutrófilos estimulados por zymosan opsonizado por ensaio imunoenzimático (ELISA). O AcAc causou um aumento na lipoperoxidação dos neutrófilos e este efeito foi dependente da sua concentração (p < 0.05; r = 0.99146); não se observou efeito do β-HOB. No estudo do efeito citotóxico, houve aumento dose-dependente da liberação da LDH até 40 mM de AcAc (p < 0.05); não se observou efeito do β-HOB. A liberação de CXCL8 foi suprimida de modo dose dependente por AcAc e β-HOB. Estes resultados sugerem que o acúmulo de corpos cetônicos pode contribuir para aumentar o tempo de remissão de doenças e mesmo estar relacionado com a gravidade destas em indivíduos diabéticos.
Lipoperoxidation, loss of cell viability and inhibition of release of IL-8 by human neutrophils in the presence of ketone bodies
Keywords: Acetoacetate; Diabetes mellitus; Interleukine-8; Lipoperoxidation; Neutrophils; 3 hydroxybutyric acid; acetoacetic acid; interleukin 8; ketone body; lactate dehydrogenase; thiobarbituric acid reactive substance; zymosan; acidosis; cell culture; cell loss; cell viability; cytokine release; cytotoxicity; enzyme linked immunosorbent assay; fatty acid metabolism; human; incubation temperature; insulin dependent diabetes mellitus; lipid peroxidation; neutrophil